Humoral and cell-mediated immune responses elicited by poly (dl-lactide) adjuvanted filarial antigen molecules. (May 2014) - Saini, Vinay; Verma, Atul Kumar; Kushwaha, Vikas; Joseph, Sujith Kurian; Kalpna Murthy, P.; Kohli, Dharmveer
Abstract Context: In our recent studies, Brugia malayi molecules have shown interesting immune-stimulating and immune-suppressive properties. Among these, F6 a pro-inflammatory (54–68 kDa) SDS-PAGE resolved fraction of the parasite when administered with Freund's complete/incomplete adjuvant in animals, elicited both Th1 and Th2 type immune responses and protects the host from filarial parasite. Objective: The present study was aimed at developing biodegradable microspheres for filarial antigenic protein molecules and to investigate the immunoadjuvanticity of microspheres (Ms)-loaded F6 molecules. Materials and methods: Poly-lactide microspheres (DL-PLA-Ms) were prepared using double emulsification and solvent evaporation method; and studied their size, shape, antigen adsorption efficiency, in-process stability, and antigen release profiles. F6 and B. malayi adult worm (BmA: ∼17 to 180 kDa) protein molecules adsorbed on the Ms were administered in a single shot into Swiss mice, subcutaneously, and investigated their immunoadjuvant effect and compared with one/two doses-schedule of plain F6/BmA. Results: Immunization with F6/BmA-loaded DL-PLA-Ms resulted in upregulation of cellular proliferation, IFN- γ, TNF-α and NO release from host's cells stimulated with F6/BmA or LPS/Con A, IgG, IgG1 and IgG2a levels. These responses were well comparable with the responses produced by two doses of plain BmA/F6. Discussion and conclusion: In conclusion, a single dose of DL-PLA-Ms-F6 induced predominantly Th1 immune responses and well comparable with two doses of plain F6. This is the first ever report on potential of DL-PLA-Ms as adjuvant for filarial immunogen.